What Is the Difference in the Risk of Suicide Death Between Spine Fracture in Patients Older Than 65 Years and Matched Controls? A Large-database Study from South Korea. Issue 11 (November 2020) - Jang, Suk-Yong; Cha, Yonghan; Kwak, Joon-Hyeok; Kim, Kap-Jung; Kim, Ha-Yong; Choy, Won-Sik
Abstract: Background: Pain and kyphotic deformity after spinal fractures can result in a decrease in a patient's physical function and quality of life. Furthermore, physical illness, such as respiratory compromise, or mental illness, including depression, may be exacerbated by a spinal fracture. Complications caused by spinal fractures and old age are risk factors for suicide, but studies on these patients are rare. Questions/purposes: (1) What is the incidence rate of death by suicide after a spinal fracture in patients older than 65 years? (2) How much does the risk of death by suicide increase in patients older than 65 years who have spine fractures compared with well-matched controls? (3) How does this risk change as a function of increasing time after injury? Methods: Spinal fractures in patients older than 65 years and matched controls were selected from the National Health Insurance Service-Senior cohort (NHIS-Senior) of South Korea. The NHIS-Senior consists of 558, 147 people selected by 10% simple random sampling method from a total of 5.5 million people 60 and older in 2002; all people were followed through 2015. A total of 31, 357 patients with spine fractures and their 62, 714 matched controls remained in the study. The mean follow-up time was 4.3 ± 3.0 years (135, 229 person-years) in the spine fracture group and 4.6 ± 3.0 years (290, 096 person-years) in the matched control group. We matched the groups for demographic factors such as age, gender, Charlson Comorbidity Index score, medication history, medical history, preoperative disability, number of hospital admissions, as well as socioeconomic factors such as household income level, residential district, and type of national health insurance using a 1:2 risk set propensity score matching by a nearest-neighbor matching algorithm with a maximum caliber of 0.1 of the hazard components. The incidence rate of suicide and the 95% confidence interval were calculated based on a generalized linear model with a Poisson distribution. The effect size was presented as a hazard ratio (HR) using Cox's proportional hazard model with robust variance estimator that accounts for clustering within matched pairs. Results: The overall risk of death by suicide throughout the surveillance period, expressed as an incidence rate, was 116 per 100, 000 person-years in spinal fracture (157 deaths by suicide over 135, 229 person-years). Throughout the entire surveillance period, the risk of death by suicide was greater among patients with spinal fractures than it was in the control group (HR 1.8 [95% CI 1.5 to 2.2]; p < 0.01). This difference was greatest in the first 365 days after the fracture (HR 2.5 [95% CI 1.6 to 3.8]; p < 0.01) (45 deaths by suicide, incidence rate: 156 per 100, 000 person-years in spinal fracture). The risk of suicide death in patients with spine fracture from 365 days to the last follow-up was also higher than that of matched controls (HR 1.6 [95% CI 1.3 to 2.1]; p < 0.01). Conclusions: Considering the substantially increased risk of death by suicide in patients with spine fractures who are older than 65 years, surgeons should consider offering psychiatric evaluation and management more frequently, particularly in patients with chronic pain, functional disability, and depressive mood. Future studies should investigate the underlying causes of suicide, such as deteriorating socioeconomic support or depression, and whether early initiation of psychological support after injury can reduce the suicide rate. Level of Evidence: Level III, prognostic study.